Assessing understandings and perceptions of HIV cure among peer navigators and treatment officers in Australia - Lau, Jillian S. Y.; Clifton, Brent; Rule, John; Ellard, Jeanne; McMahon, James H. (HIV research & clinical practice, 2024)
HIV community peer navigators and treatment officers are important sources of information and guidance for people living with HIV. We conducted an anonymous online survey with members of the treatment outreach network of the Australian National Association of People Living with HIV. The survey explored understandings and acceptance of HIV cure research and was disseminated before and following an interactive workshop on HIV cure. We demonstrated an improvement in understandings of HIV cure science and increased willingness to participate in interventional clinical trials after the workshop. Concerns around interrupting HIV treatment and detrimental impacts on health were identified as barriers to participation. Altruism was a motivator to enrol in HIV cure trials, along with endorsement from a trusted member of community.